PEDAGOGICAL WAYS OF DEVELOPING ENTREPRENEURIAL SKILLS IN THE FAMILY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the ways of organizing entrepreneurship and work in families, the structure of the development of entrepreneurial skills in children in the family, the level of development of entrepreneurial skills in the family, and the ways of forming them in young families based on the plot of a business game with its members and the analysis of the results are presented.